Dampak Penggunaan Gadget Terhadap Perkembangan Interaksi Sosial Anak Kelas VI Sekolah Dasar Inpres Mattontongdare Kec. Bajeng Barat Kab. Gowa - St Julaekha; Kasmawati K; Rudi Salam (Fatiakara Care: Jurnal Ilmiah Keperawatan, 2025)
The use of gadgets can have a negative impact, namely decreased concentration when studying, lazy writing and reading, decreased social skills, addiction, health problems, hampered children's cognitive development, inhibiting language skills, affecting children's behavior, wasting time, becoming a closed person, and threats of cyberbullying. The aim of this research is to determine the impact of gadget use on the development of social interactions in class VI children at Inpres Mattontongdare Elementary School, West Bajeng District, Gowa Regency. This research uses a cross sectional approach. This population was 156 students with a sample size of 28 students. At the Inpres Mattontongdare Elementary School, West Bajeng District, Gowa Regency. The results of this research from 28 respondents showed that 28 people (100%) used gadgets in the high category, 26 people (93%) had medium category social interaction and 2 people (7%) in the high category for Class VI children at Inpres Elementary School. Mattontongdare, West Bajeng District, Gowa District. Based on this research, the results obtained show the impact of prolonged use of gadgets on the development of social interactions in Class VI children at Inpres Mattontongdare Elementary School, West Bajeng District, Gowa Regency. Researchers suggest the role of parents in this case is to be able to control and limit the duration of gadget use so that the impact is not too severe by providig activities that enable children to reduce the duration of gadget use in a day.